Perancangan Interior Museum Film Indonesia di Surabaya - Lim Renawati Limantoro (Intra, 2013)
Surabaya is a city with a thriving cultural variety with a pluralistic society where people in Surabaya is more modern that easy to accept new things that developed in the community. Museum is a public place so that the necessary interior educative and informative and can be used as a sports-themed Indonesian films. The purpose of designing the interior of the film museum in Surabaya this is a venue to preserve Indonesian films and give knowledge to the people of Surabaya on the world of cinema and introduce the films made in Indonesia that Indonesian people not only know the movies made outside but also love movies made in the nation so that they can stimulate people to develop the quality of films and film technology in the world that continues to grow, so that Indonesia is not always left behind in the field of cinema. Design method used is descriptive method is to describe the design of the film museum objectively.